Analisa Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja pada Pekerjaan Rehabilitasi Ex-MTQ Kota Kendari - Ramadhani, Putri; Tondasi, Asrullah; Soeparyanto, Try Sugiyarto; Kadir, Ishak; Palulungan, Albert Rokky; Arsyad, La Ode Muhamad Nurrakhmad (Sultra Civil Engineering Journal (SCiEJ), 2025)
The construction sector has a high risk of workplace accidents; therefore, implementing the Occupational Safety and Health Management System (SMK3) is highly important. This study aims to analyze the implementation of SMK3 in the rehabilitation project of Ex-MTQ Kendari City using a descriptive qualitative method through observation and interviews. The results show that the implementation of SMK3 has been fairly good, as indicated by the use of personal protective equipment (PPE), safety signs, safety briefings, and the presence of safety officers on site.